Bone marrow biopsies of patients with hematopoietic and lymphoid disorders - epidemiology, chromosomal aberrations and molecular pathology - Hehne, Sophie; Deimling, Andreas von (Pathology, research and practice, 2012)
Bone marrow biopsy of the iliac crest is the first and most important step in the diagnostics of hematopoietic disorders. The biopsies of the years 2006 and 2007 from the Institute of Pathology of the Jena University Hospital were retrospectively analyzed for clinicopathological parameters. In addition, the Mitelman database was retrieved for chromosomal aberrations. The analysis of 2820 reports from 1185 patients revealed that lymphomas, plasma cell myeloma and acute leukemia were most frequent. Males predominated in myeloproliferative neoplasms and lymphoma subtypes, particularly CLL, except for plasma cell myeloma and acute leukemia. A peak incidence was seen between 61 and 70 years of age with a varying pattern for single entities. The database search revealed that ALL, AML, CLL and CML were mainly diploid while Hodgkin lymphoma, mature B-cell lymphoma and multiple myeloma mostly carried hyperdiploid chromosome numbers. Numerical aberrations like chromosome 8 gains in hyperdiploid CML were prominent in specific subgroups. Molecular testing is exemplified in CML, plasma cell myeloma and hairy cell leukemia. The study highlights typical clinicopathological characteristics and new genetic findings in hematopoietic and lymphoid neoplasms with relevance for the new WHO classification and beyond. We hope that it may help in the differential diagnosis of bone marrow biopsies.
Gesehen am 09.04.2018